MANFAAT BERKELOMPOKTANI DALAM MENINGKATKAN PENDAPATAN DAN EFISIENSI EKONOMI RELATIF USAHATANI PADI DI DESA NEGARA RATU KECAMATAN NATAR KABUPATEN LAMPUNG SELATAN - Muhammad Iqbal Kasogi; Dyah Aring Hepiana Lestari; Novi Rosanti (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2014)
This study aims to assess the benefit of being member of farmer group in improving income and relative economic efficiency on rice farm according to the comparison of farm income and the relative economic efficiency between farmer members and non-members of farmers group.  This research was conducted in Negara Ratu village of Natar Subdistrict of South Lampung Regency.  Farmer samples were selected randomly by simple random sampling. The total samples were seventy seven farmers, consisted of 38 farmer members and 39 non-farmer members.  The data was collected in February - March 2014. The benefits of farmers group was analyzed by t-test for the comparison of farm income and the profit function by adding the Dummy variable.  The results showed that the member farmer's income was higher than that of nonmembers of farmer groups. The relative economic efficiency of farmer group members were significantly higher than that of non members of farmers group, both in the first season and second season. Key words : farmer group members, relative economic efficiency, rice farming income